Silicon-carbon negative electrode material, preparation method thereof and application of silicon-carbon negative electrode material in lithium ion battery

By embedding the elastic cage-shaped carbon material core and disordered carbon layer shell of nano silicon particles in the negative electrode material of the lithium-ion battery, the volume expansion problem of silicon material during charging and discharging is solved, and a lithium-ion battery with high cycle stability and energy density is achieved.

CN119852336AActive Publication Date: 2025-04-18LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202311354865.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18
Estimated Expiration
2043-10-18

AI Technical Summary

Technical Problem

Silicon materials expand in volume due to the formation of alloys during charging and discharging of lithium-ion batteries, limiting their large-scale production and application in lithium-ion batteries.

Method used

The silicon carbon negative electrode material composed of an elastic cage-shaped carbon material core with nano-silicon particles and a disordered carbon layer shell is effectively suppressed. The preparation method of the material includes high-temperature vapor deposition and high-temperature vapor-phase coating.

Benefits of technology

The low-expanded silicon-carbon negative electrode material is achieved, which improves the cycle stability and energy density of lithium-ion batteries and extends the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852336A_ABST
    Figure CN119852336A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to a silicon-carbon negative electrode material, a preparation method and application of the silicon-carbon negative electrode material in a lithium ion battery. The silicon-carbon negative electrode material is composed of an elastic cage-shaped carbon material core deposited with nano silicon particles and a disordered carbon layer shell, a carbon material framework of the elastic cage-shaped carbon material core specifically comprises a spherical carbon molecule core structure formed by one of fullerene C60, fullerene C70 or fullerene C80, and the nano silicon particles are embedded into the core structure; the disordered carbon atoms are wrapped outside the inner core to form the disordered carbon layer shell; and the average thickness of the disordered carbon layer shell is not less than 10nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a silicon-carbon negative electrode material, a preparation method thereof, and an application thereof in lithium ion batteries. Background Art

[0002] Lithium-ion batteries have attracted much attention due to their high energy density, no memory effect, and ability to be charged and discharged multiple times. Among them, the negative electrode material is an extremely important component of lithium-ion batteries, and it is urgent to develop new lithium-ion battery negative electrode materials with high capacity and long cycle life.

[0003] Carbon materials have been widely studied as negative electrode materials for lithium-ion batteries, especially graphite negative electrode materials, which are favored by the industry due to their good conductivity and stable cycle life. However, the theoretical specific capacity of graphite negative electrode is only 372mAh / g, which seriously limits the energy density of lithium-ion batteries.

[0004] Silicon, an element of the same family as carbon, has attracted attention as anode material for lithium-ion batteries due to its ultra-high theoretical specific capacity (4200mAh / g); at the same time, silicon is abundant in the earth and will hopefully gradually replace graphite anode materials and become the mainstream of lithium-ion battery materials. However, silicon materials expand in volume due to alloy formation during the charge and discharge process, which will greatly limit the large-scale production and application of silicon materials in lithium-ion batteries.

[0005] Therefore, there is an urgent need to develop a silicon-carbon composite negative electrode material with low expansion, high capacity and high initial efficiency to solve the problem of volume expansion of silicon during the lithium ion charging and discharging process, thereby improving the cycle life of lithium ion batteries. Summary of the invention

[0006] The purpose of the present invention is to provide a silicon-carbon negative electrode material, a preparation method and an application in lithium-ion batteries. By depositing an elastic cage-like carbon material inner core with nano-silicon particles and a disordered carbon layer outer shell, the volume expansion of silicon during the charge and discharge process can be effectively suppressed, and the cycle stability of the lithium-ion battery can be further improved. The low-expansion silicon-carbon negative electrode material exhibits a higher specific capacity, which is beneficial to improving the energy density of the lithium-ion battery.

[0007] To this end, in a first aspect, an embodiment of the present invention provides a silicon-carbon negative electrode material, wherein the silicon-carbon negative electrode material is composed of an elastic cage-like carbon material core deposited with nano-silicon particles and a disordered carbon layer shell;

[0008] The carbon material skeleton of the elastic cage-like carbon material core specifically includes fullerene C 60 , C 70 or C 80One of them forms a spherical carbon molecule core structure, the nano silicon particles are embedded in the core structure; disordered carbon atoms are wrapped outside the core to form the disordered carbon layer shell; the average thickness of the disordered carbon layer shell is not less than 10nm.

[0009] In a second aspect, an embodiment of the present invention provides a method for preparing the silicon-carbon negative electrode material described in the first aspect, the preparation method comprising: sequentially performing high-temperature vapor deposition and high-temperature vapor coating under an inert atmosphere;

[0010] The high-temperature vapor deposition process comprises: placing a carbon material skeleton raw material in a high-temperature furnace, introducing a silicon source gas to deposit nano-silicon particles in the carbon material skeleton, and obtaining an elastic cage-shaped carbon material core with nano-silicon particles deposited thereon;

[0011] The high-temperature gas phase coating process includes: closing the silicon source gas, introducing the carbon source gas, and coating the surface of the elastic cage-shaped carbon material core deposited with nano-silicon particles to form a disordered carbon layer shell.

[0012] Preferably, the silicon source gas used in the high-temperature vapor deposition process is monosilane and / or disilane; the temperature of the high-temperature vapor deposition is 400°C-1000°C, and the time of the high-temperature vapor deposition is 2h-10h.

[0013] Preferably, the carbon source gas used in the high-temperature gas-phase coating process is one or more of acetylene, ethylene or propylene; the temperature of the high-temperature gas-phase coating is: 400°C-1000°C, and the time of the high-temperature gas-phase coating is 2h-10h.

[0014] Preferably, the carbon material skeleton raw material includes fullerene C 60 , C 70 or C 80 The method of introducing silicon source gas to deposit nano silicon particles in the carbon material skeleton is specifically as follows:

[0015] Silicon source gas is introduced to deposit nano-silicon particles on the fullerene C 60 , C 70 or C 80 in a cage-like structure.

[0016] In a third aspect, an embodiment of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the silicon-carbon negative electrode material described in the first aspect.

[0017] Preferably, during the charging process of the lithium-ion battery, the silicon-carbon negative electrode material is embedded with lithium, and the nano-silicon particles in the silicon-carbon negative electrode material are embedded with lithium to form a silicon-lithium alloy; during the discharging process of the lithium-ion battery, the silicon-carbon negative electrode material is de-lithiumed, and the silicon-lithium alloy is de-lithiumed and reduced to nano-silicon particles.

[0018] The silicon-carbon negative electrode material provided by the embodiment of the present invention helps to improve the specific capacity of the battery through the core structure of nano-silicon particles embedded in the elastic cage-like carbon material. This structure helps to provide higher energy storage capacity and helps to improve the energy density of lithium-ion batteries; the silicon-carbon negative electrode material adopts the structure of the elastic cage-like carbon material core and the disordered carbon layer shell, which can effectively inhibit the volume expansion of silicon and achieve low expansion, thereby improving the cycle stability of lithium-ion batteries; because the material has the characteristics of high specific capacity and inhibiting the volume expansion of silicon, it can significantly improve the performance of lithium-ion batteries, is more stable during the charging and discharging process, and is conducive to extending the life of the battery. The silicon-carbon negative electrode material provided by the present invention has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A flow chart of a method for preparing a silicon-carbon negative electrode material provided in an embodiment of the present invention;

[0020] Figure 2 A schematic diagram of the structure of the silicon-carbon negative electrode material provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0022] The embodiment of the present invention provides a silicon-carbon negative electrode material, which is composed of an elastic cage-shaped carbon material core deposited with nano-silicon particles and a disordered carbon layer shell.

[0023] The carbon material skeleton of the elastic cage-like carbon material core specifically includes fullerene C 60 , C 70 or C 80 One of them forms a core structure of spherical carbon molecules, with nano-silicon particles embedded in the core structure;

[0024] The disordered carbon atoms are wrapped around the inner core to form a disordered carbon shell; the disordered carbon atoms in the disordered carbon shell are coated thickly, with an average thickness of not less than 10 nm. The preferred coating thickness is 10 nm-20 nm.

[0025] The silicon-carbon negative electrode material of the embodiment of the present invention is obtained by sequentially performing high-temperature vapor deposition and high-temperature vapor coating of a carbon material skeleton raw material under an inert atmosphere. The main method steps can be as follows: Figure 1 The main steps include:

[0026] Step 110, placing the carbon material skeleton raw material in a high-temperature furnace, introducing silicon source gas to deposit nano-silicon particles in the carbon material skeleton, and obtaining an elastic cage-shaped carbon material core with nano-silicon particles deposited thereon;

[0027] Carbon material skeleton raw materials include fullerene C60 , C 70 or C 80 The structure of fullerene is cage-shaped (also called spherical), with C 60 For example, it is composed of 60 carbon atoms, each carbon atom is connected to the adjacent carbon atoms through carbon-carbon bonds to form a spherical structure similar to a soccer ball. These carbon atoms are arranged in hexagonal and pentagonal forms and connected together by carbon-carbon bonds to form a highly symmetrical and stable fullerene molecular structure. 60 , C 70 or C 80 It has a certain elasticity. Although it is a substructure composed of carbon atoms, it still has some elasticity to a certain extent on a microscopic scale due to the flexibility of its molecular structure and the elastic properties of carbon-carbon bonds.

[0028] The carbon source gas used in the high-temperature gas-phase coating process is one or more of acetylene, ethylene or propylene; the temperature of the high-temperature gas-phase coating is: 400°C-1000°C, and the time of the high-temperature gas-phase coating is 2h-10h.

[0029] The high-temperature gas-phase coating process deposits nano-silicon particles on the fullerene C 60 , C 70 or C 80 in a cage-like structure.

[0030] Step 120 , closing the silicon source gas and introducing the carbon source gas to coat the surface of the elastic cage-like carbon material core on which the nano-silicon particles are deposited, to form a disordered carbon layer shell.

[0031] The carbon source gas used in the high-temperature gas-phase coating process is one or more of acetylene, ethylene or propylene; the temperature of the high-temperature gas-phase coating is: 400°C-1000°C, and the time of the high-temperature gas-phase coating is 2h-10h.

[0032] The silicon-carbon negative electrode material prepared by the present invention is applied to lithium-ion batteries. During the charging process of the lithium-ion battery, the silicon-carbon negative electrode material is embedded with lithium, and the nano-silicon particles in the silicon-carbon negative electrode material are embedded with lithium to form a silicon-lithium alloy; during the discharging process of the lithium-ion battery, the silicon-carbon negative electrode material is de-lithiumed, and the silicon-lithium alloy is de-lithiumed and reduced to nano-silicon particles. 60 The specific process of forming the carbon material skeleton is shown as follows: Figure 2 shown.

[0033] The silicon-carbon negative electrode material provided by the embodiment of the present invention helps to improve the specific capacity of the battery through the core structure of nano-silicon particles embedded in the elastic cage-like carbon material. This structure helps to provide higher energy storage capacity and helps to improve the energy density of lithium-ion batteries; the silicon-carbon negative electrode material adopts the structure of the elastic cage-like carbon material core and the disordered carbon layer shell, which can effectively inhibit the volume expansion of silicon, thereby improving the cycle stability of lithium-ion batteries; because the material has the characteristics of high specific capacity and inhibiting the volume expansion of silicon, it can significantly improve the performance of lithium-ion batteries, is more stable during the charging and discharging process, and is conducive to extending the life of the battery. The low-expansion silicon-carbon negative electrode material provided by the present invention has good application prospects.

[0034] In order to more clearly illustrate the purpose and advantages of the present invention, the present invention is further described below in conjunction with the embodiments. In addition, the embodiments described in the present invention are only partial embodiments. Based on the embodiments described in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the protection scope of the present invention. In addition, it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.

[0035] Example 1

[0036] This embodiment provides a method for preparing a low-expansion silicon-carbon negative electrode material.

[0037] Step 1, high temperature vapor deposition: 5 kg of C 60 Carbon substrate raw material, nitrogen with a flow rate of 30L / min was introduced to purge the furnace body to form an inert protective atmosphere; after ventilation for half an hour, the temperature began to rise, and the temperature of the deposition furnace was raised to 600°C at a heating rate of 3°C / min, and the temperature was maintained for 30 minutes to stabilize the furnace temperature; then monosilane was introduced, and nitrogen was continued to be introduced at the same time, so that the gas flow rate ratio of monosilane and nitrogen was 20L / min:30L / min, and the insulation time was 5h, monosilane was cracked, SiH bonds were broken, hydrogen and silicon atoms were released, and the generated nano-silicon particles were deposited on C 60 In the carbon material skeleton, an elastic cage-shaped carbon material core with nano-silicon particles deposited thereon is obtained.

[0038] Step 2, high temperature gas phase coating: C 60 The conductive carbon substrate was placed in the deposition furnace, monosilane was turned off, propylene was introduced, the nitrogen flow rate was adjusted to make the gas flow rate ratio of nitrogen and propylene 8L / min:8L / min, the insulation temperature was 600℃, the insulation time was 8h, propylene was decomposed, and the C substrate with nano-silicon deposited was 60A disordered carbon layer shell is formed on the surface of the conductive carbon substrate to obtain a low-expansion silicon-carbon negative electrode material.

[0039] The negative electrode sheet was prepared with the low expansion silicon-carbon negative electrode material obtained in the deposition furnace, and the button half-cell was assembled for testing, as follows:

[0040] The obtained low expansion silicon carbon negative electrode material, conductive agent Super P and binder carboxymethyl cellulose (CMC) were fully ground in a mortar at a mass ratio of 8:1:1, and then deionized water was added to form a slurry, which was coated on the copper foil current collector and dried in a vacuum oven at 80°C for 12 hours. The dried electrode was then cut into discs with a diameter of 12 mm as the negative electrode of the lithium-ion battery.

[0041] The counter electrode of the button half-cell is a lithium sheet, and the electrolyte used is an aqueous electrolyte, specifically 1M Li PF6@ethylene carbonate (EC) / dimethyl carbonate (DMC) / diethyl carbonate (DEC), with a volume ratio of v / v / v=1:1:1, and assembled into a button half-cell in a glove box. Finally, it was tested on the Blue Battery Test System to evaluate its electrochemical performance. The half-cell was tested in a constant current charge and discharge mode, with a discharge cut-off voltage of 0.005V and a charge cut-off voltage of 2V. The test data of the capacity retention rate and the first coulombic efficiency after 500 cycles at a rate of 0.5C are shown in Table 1.

[0042] Example 2

[0043] Step 1, high temperature vapor deposition: 5 kg of C 70 Carbon substrate raw material, nitrogen with a flow rate of 30L / min was introduced to purge the furnace body to form an inert protective atmosphere; after ventilation for half an hour, the temperature began to rise, and the temperature of the deposition furnace was raised to 600°C at a heating rate of 3°C / min, and the temperature was maintained for 30min to stabilize the furnace temperature; then monosilane was introduced, and nitrogen was continued to be introduced at the same time, so that the gas flow rate ratio of monosilane and nitrogen was 20L / min:30L / min, and the insulation time was 5h, monosilane was cracked, SiH bonds were broken, hydrogen and silicon atoms were released, and the generated nano-silicon particles were deposited on C 70 In the carbon material skeleton, an elastic cage-shaped carbon material core with nano-silicon particles deposited thereon is obtained.

[0044] Step 2, high temperature gas phase coating: C 70 The conductive carbon substrate was placed in the deposition furnace, monosilane was turned off, propylene was introduced, the nitrogen flow rate was adjusted to make the gas flow rate ratio of nitrogen and propylene 8L / min:8L / min, the insulation temperature was 600℃, the insulation time was 8h, propylene was decomposed, and the C substrate with nano-silicon deposited was 70A disordered carbon layer shell is formed on the surface of the conductive carbon substrate to obtain a low-expansion silicon-carbon negative electrode material.

[0045] The negative electrode sheet was prepared using the low expansion silicon-carbon negative electrode material obtained in the deposition furnace, and button-type half-cells were assembled for testing in the same manner as in Example 1. The test data are shown in Table 1.

[0046] Example 3

[0047] Step 1, high temperature vapor deposition: 5 kg of C 80 Carbon substrate raw material, nitrogen with a flow rate of 30L / min was introduced to purge the furnace body to form an inert protective atmosphere; after ventilation for half an hour, the temperature began to rise, and the temperature of the deposition furnace was raised to 600°C at a heating rate of 3°C / min, and the temperature was maintained for 30min to stabilize the furnace temperature; then monosilane was introduced, and nitrogen was continued to be introduced at the same time, so that the gas flow rate ratio of monosilane and nitrogen was 20L / min:30L / min, and the insulation time was 5h, monosilane was cracked, SiH bonds were broken, hydrogen and silicon atoms were released, and the generated nano-silicon particles were deposited on C 80 In the carbon material skeleton, an elastic cage-shaped carbon material core with nano-silicon particles deposited thereon is obtained.

[0048] Step 2, high temperature gas phase coating: C 80 The conductive carbon substrate was placed in the deposition furnace, monosilane was turned off, propylene was introduced, the nitrogen flow rate was adjusted to make the gas flow rate ratio of nitrogen and propylene 8L / min:8L / min, the insulation temperature was 600℃, the insulation time was 8h, propylene was decomposed, and the C substrate with nano-silicon deposited was 80 A disordered carbon layer shell is formed on the surface of the conductive carbon substrate to obtain a low-expansion silicon-carbon negative electrode material.

[0049] The negative electrode sheet was prepared using the low expansion silicon-carbon negative electrode material obtained in the deposition furnace, and button-type half-cells were assembled for testing in the same manner as in Example 1. The test data are shown in Table 1.

[0050] Example 4

[0051] Step 1, high temperature vapor deposition: 5 kg of C 60 Carbon substrate raw material, nitrogen gas with a flow rate of 20L / min was introduced to purge the furnace body to form an inert protective atmosphere; after ventilation for half an hour, the temperature began to rise, and the temperature of the deposition furnace was raised to 900°C at a heating rate of 5°C / min, and the temperature was maintained for 30 minutes to stabilize the furnace temperature; then disilane was introduced, and nitrogen was continued to be introduced at the same time, so that the gas flow rate ratio of disilane and nitrogen was 20L / min:20L / min, and the insulation time was 5h, disilane was cracked, SiH bonds were broken, hydrogen and silicon atoms were released, and the generated nano-silicon particles were deposited on C60 In the carbon material skeleton, an elastic cage-shaped carbon material core with nano-silicon particles deposited thereon is obtained.

[0052] Step 2, high temperature gas phase coating: C 60 The conductive carbon substrate was placed in the deposition furnace, disilane was turned off, acetylene was introduced, the nitrogen flow rate was adjusted to make the gas flow rate ratio of nitrogen and acetylene 10L / min:8L / min, the insulation temperature was 900℃, the insulation time was 4h, acetylene was decomposed, and the C substrate with nano-silicon deposited was 60 A disordered carbon layer shell is formed on the surface of the conductive carbon substrate to obtain a low-expansion silicon-carbon negative electrode material.

[0053] Example 5

[0054] Step 1, high temperature vapor deposition: 5 kg of C 60 Carbon substrate raw material, nitrogen with a flow rate of 20L / min was introduced to purge the furnace body to form an inert protective atmosphere; after ventilation for half an hour, the temperature began to rise, and the temperature of the deposition furnace was raised to 800°C at a heating rate of 5°C / min, and the temperature was maintained for 30 minutes to stabilize the furnace temperature; then disilane was introduced, and nitrogen was continued to be introduced at the same time, so that the gas flow rate ratio of disilane and nitrogen was 20L / min:20L / min, and the insulation time was 5h, disilane was cracked, SiH bonds were broken, hydrogen and silicon atoms were released, and the generated nano-silicon particles were deposited on C 60 In the carbon material skeleton, an elastic cage-shaped carbon material core with nano-silicon particles deposited thereon is obtained.

[0055] Step 2, high temperature gas phase coating: C 60 The conductive carbon substrate was placed in the deposition furnace, disilane was turned off, the temperature was lowered to 600°C, and the temperature was kept for 15 minutes. Then ethylene was introduced, and the nitrogen flow rate was adjusted so that the gas flow rate ratio of nitrogen and ethylene was 8L / min:8L / min. The temperature was kept at 600°C for 6 hours. Ethylene was decomposed. 60 A disordered carbon layer shell is formed on the surface of the conductive carbon substrate to obtain a low-expansion silicon-carbon negative electrode material.

[0056] Comparative Example 1

[0057] Step 1, put 5 kg of conductive carbon black as the carbon substrate raw material into the deposition furnace, and introduce nitrogen at a flow rate of 30 L / min to form a protective atmosphere; start heating after ventilation for half an hour, increase the temperature of the deposition furnace to 600°C at a heating rate of 3°C / min, and maintain the temperature for 30 minutes; then introduce monosilane and nitrogen, the gas flow rate ratio is 20 L / min:30 L / min, and the insulation time is 5 hours.

[0058] Step 2: The conductive carbon black carbon substrate with silicon deposited thereon is placed in the deposition furnace, monosilane is turned off, propylene is introduced, the nitrogen flow rate is adjusted so that the gas flow rate ratio of nitrogen and propylene is 8 L / min:8 L / min, the insulation temperature is 600°C, and the insulation time is 8 hours to obtain the negative electrode active material.

[0059] The active material obtained in the deposition furnace was used as the negative electrode material of the lithium ion battery to assemble a button cell for testing, and the method was the same as that of Example 1. The test data is shown in Table 1.

[0060] Comparative Example 2

[0061] Step 1, put 5 kg of carbon nanotubes as carbon substrate raw materials into the deposition furnace, and introduce nitrogen at a flow rate of 30 L / min to form a protective atmosphere; start heating after ventilation for half an hour, increase the temperature of the deposition furnace to 600°C at a heating rate of 3°C / min, and maintain the temperature for 30 minutes; then introduce monosilane and nitrogen, the gas flow rate ratio is 20 L / min:30 L / min, and the insulation time is 5 hours.

[0062] Step 2: The conductive carbon black carbon substrate with silicon deposited thereon is placed in the deposition furnace, monosilane is turned off, propylene is introduced, the nitrogen flow rate is adjusted so that the gas flow rate ratio of nitrogen and propylene is 8 L / min:8 L / min, the insulation temperature is 600°C, and the insulation time is 8 hours to obtain the negative electrode active material.

[0063] The active material obtained in the deposition furnace was used as the negative electrode material of the lithium ion battery to assemble a button cell for testing, and the method was the same as that of Example 1. The test data is shown in Table 1.

[0064] Table 1 is a comparison of the capacity retention and the first coulombic efficiency of the lithium-ion button half-cells prepared in Examples 1-3 and Comparative Examples 1-2 after 500 cycles at a rate of 0.5C.

[0065] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Cycle retention rate 95.5% 90.1% 92.4% 33.3% 45.0% First coulombic efficiency 92.6% 91.8% 92.1% 88.0% 83.5%

[0066] Table 1

[0067] From the comparative data of the capacity retention rate and the first coulombic efficiency of the lithium ion button half-cells prepared in the examples and comparative examples in Table 1 after 500 cycles at a rate of 0.5C, it can be seen that when the silicon-carbon active materials in Examples 1-3 prepared by the one-step scheme of high-temperature vapor deposition and high-temperature vapor coating are used as the negative electrode materials of lithium ion half-cells, their cycle stability is far better than that of the silicon-carbon negative electrode materials in Comparative Examples 1-2; at the same time, the first coulombic efficiency in Examples 1-3 is higher than that in Comparative Examples 1-2. It can be seen that by selecting a cage-shaped conductive carbon substrate as the substrate for depositing nano-silicon, the volume expansion of silicon during the charge and discharge process can be effectively slowed down, thereby greatly improving the cycle stability and the first coulombic efficiency of lithium ion batteries.

[0068] The present invention provides a method for preparing a silicon-carbon negative electrode material, wherein C 60 , C 70 and C 80 The core conductive matrix represented by is nano-silicon deposited into the interior of the elastic cage-like matrix by high-temperature vapor deposition, which reserves enough space for the volume expansion of silicon after alloying, and can effectively solve the volume expansion problem of silicon during the charging and discharging process; further, by coating with a thicker disordered carbon shell, the cage-like substrate on which nano-silicon is deposited can be closed, thereby improving its first coulombic efficiency.

[0069] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A silicon-carbon negative electrode material, characterized in that: The silicon-carbon negative electrode material is composed of an elastic cage-shaped carbon material core deposited with nano-silicon particles and a disordered carbon layer shell; The carbon material skeleton of the elastic cage-like carbon material core specifically includes fullerene C 60 , C 70 or C 80 One of them forms a spherical carbon molecule core structure, and the nano silicon particles are embedded in the core structure; The disordered carbon atoms are wrapped around the inner core to form the disordered carbon layer shell; the average thickness of the disordered carbon layer shell is not less than 10 nm.

2. A method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: The preparation method comprises: sequentially performing high-temperature vapor phase deposition and high-temperature vapor phase coating in an inert atmosphere; The high-temperature vapor deposition process comprises: placing a carbon material skeleton raw material in a high-temperature furnace, introducing a silicon source gas to deposit nano-silicon particles in the carbon material skeleton, and obtaining an elastic cage-shaped carbon material core with nano-silicon particles deposited thereon; The high-temperature gas phase coating process includes: closing the silicon source gas, introducing the carbon source gas, and coating the surface of the elastic cage-shaped carbon material core deposited with nano-silicon particles to form a disordered carbon layer shell.

3. The preparation method according to claim 2, characterized in that: The silicon source gas used in the high-temperature vapor deposition process is monosilane and / or disilane; the temperature of the high-temperature vapor deposition is: 400°C-1000°C, and the time of the high-temperature vapor deposition is 2h-10h.

4. The preparation method according to claim 2, characterized in that: The carbon source gas used in the high-temperature gas-phase coating process is one or more of acetylene, ethylene or propylene; the temperature of the high-temperature gas-phase coating is: 400°C-1000°C, and the time of the high-temperature gas-phase coating is 2h-10h.

5. The preparation method according to claim 2, characterized in that: The carbon material skeleton raw material includes fullerene C 60 , C 70 or C 80 The method of introducing silicon source gas to deposit nano silicon particles in the carbon material skeleton is specifically as follows: Silicon source gas is introduced to deposit nano-silicon particles on the fullerene C 60 , C 70 or C 80 in a cage-like structure.

6. A lithium ion battery, characterized in that: The lithium-ion battery comprises the silicon-carbon negative electrode material as described in claim 1 above.

7. The lithium-ion battery according to claim 6, characterized in that: During the charging process of the lithium-ion battery, the silicon-carbon negative electrode material is embedded with lithium, and the nano-silicon particles in the silicon-carbon negative electrode material are embedded with lithium to form a silicon-lithium alloy; during the discharging process of the lithium-ion battery, the silicon-carbon negative electrode material is de-lithiumed, and the silicon-lithium alloy is de-lithiumed and reduced to nano-silicon particles.

Citation Information

Patent Citations

  • Silicon-carbon composite negative electrode material for lithium ion battery and preparation method thereof

    CN103474667A

  • Silicon-carbon composite material of closed cage structure and preparation method of silicon-carbon composite material of closed cage structure

    CN107863513A

  • Negative electrode material and battery comprising same

    CN114335533A

  • Cage-shaped silicon-carbon composite material, preparation method thereof, battery negative electrode and battery

    CN114824279A

  • Nano Si-C-G composite negative electrode material, preparation method and lithium ion battery

    CN116565185A